Sexual harassment prevention application with a Moerija Cultural approach for students with special needs - Savitri Wanabuliandari; Sekar Dwi Ardianti; Evanita Evanita (University of Merdeka Malang, 2024)
In Indonesia, the government is trying to safeguard and protect children from sexual crimes. Sexual crimes are particularly vulnerable to students with special needs. These students have limitations and minimal access to sexual education, making them frequent targets of sexual harassment and abuse. Students with special needs are at a higher risk of becoming victims of sexual violence due to their unique vulnerabilities. The impact of such abuse includes inferiority, anxiety, panic, and even depression. This must be addressed immediately, as it can disrupt the psychological and emotional development of students with special needs, hindering their potential to thrive and compete in the increasingly competitive digital era. The aim of this community service activity is to provide digital media with a local Moerija cultural approach to introduce sexual and application-based education. The method used in these community service activities is participant active learning, ensuring engagement and practical application. The results obtained are the development of an application designed to prevent sexual violence, utilizing a culturally relevant Moerija approach to raise awareness and enhance protective measures.